Examining the roles of Duolingo Application as a learning tool in promoting efl learners' autonomy - Fauziah, Afni Afifah; Williyan, Aldha; Rosalina, Utami (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2024)
This study aims to explore the role of the Duolingo app in increasing students' English language learning independence. Data was collected through interviews with five participating students over two weeks in May 2024. The results showed that the majority of students enjoy using the mobile app to learn English because it is effective, fun, and allows learning anytime and anywhere. Some students highlighted that the app provides engaging content such as text, audio and video which enhances their learning experience. Most students know Duolingo from teachers, social media such as Instagram, and personal use. Their first impressions of Duolingo are very positive, mainly due to its attractive design and fun learning experience. After using Duolingo, students feel that the app is effective in helping them expand their vocabulary and understand basic grammar. Duolingo's interactive and engaging design also increases their motivation to learn. Students feel motivated by the daily targets and reward system in Duolingo. Gamification features such as points, levels and daily streaks make them more eager to learn every day. Most students use Duolingo to prepare for study abroad in the hope of strengthening their English skills so as not to face communication difficulties. The features most appreciated by students are the immediate feedback and the variety of language courses. Duolingo helps students learn independently by providing a variety of topics, flexible access, and a structured curriculum. Some students report significant improvements in listening, speaking, and vocabulary skills after using Duolingo. Features such as points, levels, streaks, feedback, daily challenges, and listening and vocabulary exercises are what motivate students to continue learning the most. This research shows that Duolingo can increase students' learning independence by creating a fun and challenging learning environment and providing flexibility in the learning process